UNIVERSALITY OF BROWN AND LEVINSON POLITENESS THEORY IN COLLECTIVE CULTURE: REDEFINING POWER IN CONCEPT OF FACE - Nuraini (EJI (English Journal of Indragiri) : Studies in Education, Literature, and Linguistics, 2021)
The claim of universality of Brown and Levinson's theory of politeness has encouraged the theory's debate to draw the concept of face in group society culture. This article analyzes the concept of face in several group societies claiming that Brown and Levinson missed covering. The analysis was described through library research using primary and secondary data. The primary data comes from the original book of Politeness Theory written by Brown and Levinson. The secondary data were the description and the example of the conversation, how the existence of linguistics set of a language, and the ritual of performing an interaction in the culture found in some articles supporting and debating Brown and Levinson's universality Politeness theory. This analysis concludes that Brown and Levinson's Theory covered the group society politeness and face concept by seeing the definition of power imposition on society members. While the theory of Brown and Levinson is flawed to explain the flip concept of face in a collective culture, computing the weightiness of FTAs formula has covered the role of culture and group situational interaction. It makes this concept can be applied to any cross-cultural boundary universally.